1997
DOI: 10.1007/s004180050162
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin undergoes rapid dephosphorylation in stimulated neutrophils and translocates to ruffled membranes enriched in products of the NADPH oxidase complex. Evidence for a novel cycle of phosphorylation and dephosphorylation

Abstract: Neutrophils contain a 21-kDa phosphoprotein that undergoes rapid dephosphorylation upon stimulation of these cells with the chemoattractant N-fMet-Leu-Phe (fMLP), activators of protein kinase C [e.g., 4 beta-phorbol 12-myristate 13-acetate (PMA)] or the calcium ionophore A23187. This phosphoprotein was identified as the non-muscle form of cofilin by peptide sequencing and immunoblotting with specific antibodies. Evidence is presented that in neutrophils cofilin is regulated by a continual cycle of phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 63 publications
7
61
2
Order By: Relevance
“…This is in contrast to the transferrin receptor, a nonraft localized receptor associated with the cell membrane, whose membrane association was not altered by U73122 treatment. These results are in accordance with other reports that indicate that a portion of cofilin is associated with the cell periphery (Suzuki et al, 1995;Heyworth et al, 1997). Interestingly, we also found that transfection of EphA4 alone could reduce the levels of cofilin found in the membrane fraction.…”
Section: Plc Signaling Is Necessary For Ephrininduced Spine Shrinkagesupporting
confidence: 94%
“…This is in contrast to the transferrin receptor, a nonraft localized receptor associated with the cell membrane, whose membrane association was not altered by U73122 treatment. These results are in accordance with other reports that indicate that a portion of cofilin is associated with the cell periphery (Suzuki et al, 1995;Heyworth et al, 1997). Interestingly, we also found that transfection of EphA4 alone could reduce the levels of cofilin found in the membrane fraction.…”
Section: Plc Signaling Is Necessary For Ephrininduced Spine Shrinkagesupporting
confidence: 94%
“…Oxidant production is also most prominent in actively migrating endothelial cells at the margin of a monolayer wound and, in particular, is concentrated in membrane ruffles of these highly motile cells (10). This localization of oxidant production is comparable to that found in phorbol-ester-stimulated neutrophils whose oxidative burst is concentrated within ruffling membranes (11). Consistent with these observations, we recently found constitutive localization of the NADPH oxidase subunit p47 phox to the cytoskeleton of endothelial cells with translocation of p47-GFP to membrane ruffles (12).…”
mentioning
confidence: 56%
“…In recent studies, it has been shown that human cofilin forms oligomers, which exhibit actin severing activity, and human cyclase-associated protein-1 is a key factor in the recycling of cofilin and actin (9,10). It has been reported that in some cell types, the dephosphorylation of cofilin occurs in a calcium-dependent or -independent manner and accompanies nuclear uptake (11)(12)(13)(14)(15)(16)(17)(18). On the other hand, dephosphorylation without nuclear uptake occurs in thyroid cells, and nuclear accumulation without dephosphorylation occurs in myotubes (19,20).…”
mentioning
confidence: 99%